The Impact of EU Politicisation on Voting Behaviour in Europe - Costa Lobo, Marina (Palgrave Studies in European Union Politics, 2023)
"This book makes a major contribution to our understanding of how the European Union influences national politics and how the national response to Europe can serve as a channel of accountability in the European Union. The authors engage fundamental questions relating to national elections and European issues with an eye to explaining the dynamics of EU political support and opposition in Belgium, Germany, Greece, Ireland, Portugal and Spain. The authors come to grips with these questions using extensive original data on EU coverage in the national media, parliamentary debates, and online surveys. In short, this volume is a signal contribution to our understanding of EU politicization." -- Gary Marks, Burton Craige Professor, UNC Chapel Hill, USA, and Professor, Robert Schuman Centre, EUI, Italy. This open access book focuses on the importance that EU politicization has gained in European democracies and the consequences for voting behaviour in six countries of the EU: Belgium, Germany, Greece, Ireland, Portugal and Spain. Most of the studies which research the way the EU is being legitimised focus on the European Parliament elections. In this book we argue that to understand how EU accountability works, it is necessary to focus instead on national elections and the national political environment. Through a detailed, multimethod analysis this book establishes rigorously the paths of European accountability at the national level, its propitious contexts in the media and parliamentary debates, and whether the paths are similar from Greece to Germany. The findings have implications for both national and European Union democracy, underlining the importance that national institutions have in enabling citizens to hold the EU accountable. Marina Costa Lobo is Research Professor at the Institute of Social Sciences of the University of Lisbon in Portugal, and Director of the European Political Science Review.